Aplicação de indicadores do modelo força motriz pressão, estado, impacto, resposta - DPSIR: subsídios para o planejamento e gestão da bacia hidrográfica do Rio São Gonçalo - CE - Landim Neto, Francisco Otávio (2016)
The hydrographic Basin São Goncalo sectors of Municipalities of Caucaia, Maranguape, Palmácia, Paracuru, Pentecoste and São Goncalo do Amarante, is undergoing a series of environmental changes resulting from the action of various agents. Thus, the present study was to i) aims to analyze the environmental systems of the watershed of the São Gonçalo in order to support the proposition of guidelines for planning and management from the definition of environmental indicators, ii) characterize the spatio-temporal systems environmental in the period 1985-2015 of the basin, with the technical benefits of remote sensing and GIS; iii) identify the environmental impacts arising from anthropogenic activities, specifying the types of land use, as well as the main causative agents of environmental degradation; iv) analyze the set of indicators of Driving Force model, Pressure, State, Impact and Responses - DPSIR as a tool to support decision-making within public policies, v) provide theoretical and methodological contributions to the development of environmental predictions for building scenarios by using the DPSIR model. The methodological procedures were based on the theoretical framework consisting of studies relating to the set of indicators present in the DPSIR model (Driving Forces, Pressures, State, Impact, Responses) and technical procedures that are related to the acquisition and processing of cartographic products (work in office) and execution of field work for the validation and correction of data. From the foregoing it was found that i) the basin has an environmental dynamics that covers landscapes inherent to crystalline mountains, backwoods depression and coastal plain, also presents a dynamic of socioeconomic activities; ii) the environmental assessment made effective from the combination of the mentioned model of indicators led to present an overview of the pressures, state verification and impact enabling the formulation of actions aimed at planning and management of the basin, and vi) effected the construction of a conceptual basis inherent theoretical and methodological concepts of environmental predictions in watersheds subsidized Model DPSIR. It can be argued that the applicability of the model DPSIR indicators appears to be of great importance because it provided an integrated analysis of environmental problems, still included the purposeful actions that can be fostered by government, civil society and economic sectors.